2018
DOI: 10.1371/journal.pone.0196204
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-dependent proteolysis of CXCL7 leads to posterior longitudinal ligament ossification

Abstract: Ossification of the posterior longitudinal ligament (OPLL), a spinal ligament, reduces the range of motion in limbs. No treatment is currently available for OPLL, which is why therapies are urgently needed. OPLL occurs in obesity, is more common in men, and has an onset after 40 years of age. The mechanisms underlying OPLL remain unclear. In this study, we performed a serum proteomic analysis in both OPLL patients and healthy subjects to identify factors potentially involved in the development of OPLL, and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Some researchers have proposed that, combining pixel information of different scales can extract the best size information; some researchers believe that, reducing the size of the convolution kernel can improve the running speed of the neural network. [7][8][9][10] The CT image reconstruction algorithm can effectively remove image noise and improve image quality, assisting physicians in diagnosing diseases. With the rapid development of deep learning, many deep learning networks are used to process CT images.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have proposed that, combining pixel information of different scales can extract the best size information; some researchers believe that, reducing the size of the convolution kernel can improve the running speed of the neural network. [7][8][9][10] The CT image reconstruction algorithm can effectively remove image noise and improve image quality, assisting physicians in diagnosing diseases. With the rapid development of deep learning, many deep learning networks are used to process CT images.…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that individuals with metabolic disorders present osteoporosis, with stiffening and thickening of the posterior longitudinal ligament from the age of forty years. However, there are not any data to indicate the onset of morphological changes after instilling injury 32,33 . Since changes have been observed that point to a reduction in the thickness of the ALL, it may be an indication of positive effects, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, we induced the growth of ligament-like tissue from mesenchymal stem cells [ 1 ] and created a mouse model for ossification of the posterior longitudinal ligament (OPLL) for the study of ligament diseases [ 2 ]. In transgenic mice, ligament-like tissue derived from mesenchymal stem cells was found to be strongly expressed in the spinal ligament, anterior cruciate ligament of the knee joint, and periodontal ligament.…”
Section: Introductionmentioning
confidence: 99%
“…OPLL is an incurable disease of unknown cause in which the spinal ligament ossifies, resulting in limited range of motion and reduced function of the extremities. A previous proteomic study [ 2 ] identified a partial defect in the chemokine C-X-C motif ligand 7 (CXCL7) and low serum levels among patients. OPLL is classified into continuous, segmental, mixed, and circumscribed subtypes.…”
Section: Introductionmentioning
confidence: 99%